Ease of Use and Attitude to Optimize Purchase Intention: Study of Ride-Hailing Consumers - Siska Rahmawati; Endy Gunanto Marsasi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Various types of public transportation are available in the environment, but ride-hailing services remain the primary choice for customers. This study examines the role of perceived usefulness, perceived ease of use, and attitude in maximizing purchase intention based on the Technology Acceptance Model (TAM), which explains how users come to accept and use technology based on its perceived benefit and usability. The research focuses on ride-hailing services among generations Y and Z. The research applied a quantitative methodology and purposive sampling technique, collecting 176 samples. The data were analyzed using structural equation modelling (SEM) with SPSS 29 and AMOS Graphics 26 software, as SEM is particularly suitable for examining complex relationships between multiple variables simultaneously. The novelty of this research is the addition of attitude variables as a mediating factor, an aspect that has been underexplored in previous TAM studies within ride-hailing contexts. The results showed that perceived ease of use does not affect user satisfaction with ride-hailing services, and a significant negative effect of attitude on purchase intention was found. These findings can help service providers set strategies to improve perceived ease of use and consumer attitudes toward ride-hailing services and facilitate the implementation of marketing strategies in the future.